Тепло- и массообмен в каналах с сеточным покрытием плёнки жидкости при противоточном движении газа - Письменный, Е. Н.; Туз, В. Е.; Лебедь, Н. Л. (Eastern-European Journal of Enterprise Technologies, 2009)
The questions of passive intensification of processes of heat-mass exchange, what are going in contact vehicles are considered. Research of pellicle flow on surfaces with net coverage at the counter-current interaction with a gas stream allowed considerably to extend the range of work of vehicles, limited by hydrodynamic crises, related to beginning of overturning of flow of tape and its break